Pertumbuhan dan Hasil Tanaman Kubis Bunga (Brassica oleracea L. var. Botrytis subvar. Cauliflora DC.) Kultivar Orient F1 Akibat Jenis Mulsa dan Dosis Bokashi. - Rommy Andhika Laksono (Faculty of Agriculture University of Singaperbangsa Karawang, 2016)
ABSTRACTThis study aims to assess the growth and yield of cauliflower cultivar Orient F1 Caused by Type of Mulch and Dose Bokashi, and to find the optimal dose of bokashi on each type of mulch that can deliver maximum results. The experiments were conducted in the Telagadesa (KIIC) Sirnabaya village, District East Telukjambe of Karawang regency with a height of approximately 50 m above sea level. The experiment was conducted at the March to May 2014.Experimental method used was Split Plot Design with twelve treatments repeated three times. As the main plot was mulch type (M) consisted of three levels, no mulch (m0), straw mulch (m1), plastic black silver mulch (m2). While as the subplot was a dosage bokashi (B) consisted of four levels, 0 t ha-1 bokashi (b0), 5 t ha-1 bokashi (b1), 10 t ha-1 bokashi(b2), and 15 t ha-1 bokashi (b3).The results showed that there was an interaction the mulch type and dose of bokashi on plant height 14, 21, 28, 35 days after planting, leaf number 14, 21, 28, 35 days after planting, the diameter of the rod 21, 28, 35 days after planting, curd diameter, gross weight curd per plant, net weight curd per plant, gross weight curd per plot, and net weight curd per plot cauliflower plants Orient F1 cultivar. The highest results achieved by straw mulch with optimum dose 10,4 t ha-1 bokashi give maximum yield of 14,4 t ha-1 cauliflower.